Reforming “The Blob”: Why California’s Latest Approach to Amending CEQA Is a Bad Idea - Mackey, Katherine V. (Columbia Journal of Environmental Law, 2019)
The story of Moe’s Stop, a small gas station in San Jose, demonstrates a major problem with the California Environmental Quality Act (“CEQA”). The owner of Moe’s wanted to add three new pumps to his existing station—an action without any obvious environmental effects—but the owner of a rival gas station across the street used CEQA to convince a judge to order an environmental review of the project, which halted construction for two years. After the completion of the environmental review, Moe added the new pumps, but the rival owner still went back to court to argue that the environmental review had been flawed. The mayor of San Jose, an environmental lawyer, stated that the lawsuit was “ridiculous” and described it as “obviously anticompetitive” in its intent. The cost to the owner of Moe’s of the litigation and associated delays was over 1 million. This story of CEQA abuse is not at all unique; it demonstrates just one facet of what legislators and business advocates claim are the myriad negative economic effects of CEQA. ... This Note argues that although CEQA does have inefficiency problems, bills creating procedural constraints are not an effective way to address them. Although the laws do reduce the length of judicial review, they add other sources of inefficiency, reduce the quality of judicial review, and fail to address vague standards in CEQA that increase the difficulty of EIR preparation and judicial review. California is contemplating further changes to CEQA in 2014. But although several different reform proposals have been made, more research is necessary before deciding on the best way to amend CEQA. Part I of this Note discusses the relevant provisions of CEQA and recent attempts to change the procedure for judicial review. Part II analyzes the efficiency problems with CEQA and argues that procedural changes are a poor solution to these problems. Part III presents reform proposals and argues that before reform is attempted, more research on CEQA must be done.